INSTAGRAM SEBAGAI MEDIA PROMOSI DINAS KEBUDAYAAN DAN KEPARIWISATAAN SULAWESI SELATAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study aims to describe and analyze the use of Instagram as a media for tourist attraction promotion, and to present Instagram features in the process of promoting tourism by the Culture and Tourism Office of South Sulawesi Province. Qualitative research methods, reading social reality by means of initial observation and analyzing it. Then researchers theorize the findings. This research uses descriptive research. The results of this study indicate that the Disbudpar of South Sulawesi uses Instagram as a promotional media, and is also used as a media of information about the activities that have been carried out or to be carried out. From the overall findings, the researchers considered that the @budparsulsel account was quite good at promoting via Instagram social media even though there were some features that were not used.